School Mindfulness-Based Interventions for Youth, and Considerations for Anxiety, Depression, and a Positive School Climate-A Systematic Literature Review - Jessica Monsillion; Rafika Zebdi; Lucia Romo-Desprez (MDPI AG, 2023)
Mindfulness-based interventions (MBIs) are growing in popularity, with research concerning their efficacy with youth populations. Following a preliminary analysis of the existing literature, and given the positive effects of such programs, we felt it relevant to assess whether research has considered the implications for MBIs on children and adolescents, with regard to depression, anxiety, and school climate. Objectives: We aim to estimate the effect of MBIs as innovative interventions addressing youths in school settings, with special consideration for anxiety, depression, and school climate outcomes. Method: This review investigates the existing literature in the field of mindfulness, using quasi-experimental and randomized control trial (RCT) models, targeted at youth (5-18 years) in school settings. A search was carried out in four databases-WebofScience, Google Scholar, PubMed, and PsycARTICLES. This resulted in 39 articles, which were sorted based on predetermined inclusion criteria; 12 articles qualified. Results: The results show discrepancies in terms of methodological and implementation variables, types of interventions, instructor trainings, assessment measures, and choice of practices and exercises, which make the effects of existing school MBIs difficult to compare. Consistencies were observed in emotional and behavioral regulation, prosocial behaviors, and reducing stress and anxiety in students. The results of this systematic review also suggest that MBIs could be potential mediators in improving student well-being and environmental factors, such as school and class climates. Specifically, children's sense of safety and community can be improved by an improved quality of relationships between students, their peers, and teachers. Future research should consider incorporating school climate perspectives, such as implementing whole-school MBI approaches and using replicable and comparable study designs and methods, whilst considering the capacities and limitations of the academic and institutional context.